1980
DOI: 10.1029/ja085ia08p04223
|View full text |Cite
|
Sign up to set email alerts
|

The chemistry of excited NO+ in an aurora

Abstract: The six most significant production and seven most significant loss mechanisms are identified for NO+(a³Σ) in the aurora. Rate constants are given for these reactions as well as for the 14 most important reactions competing with the production of NO+(a). Using available data and certain crucial deductions on chemical reaction rates to simulate a number of altitude profiles, we have concluded that the two predominant sources of NO+(a3Σ) are probably N+ + O2 → NO+(a) + O and N2+ + NO → NO+(a) + N2. Radiative dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1982
1982
1998
1998

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…The cation of the NO molecule NO + is one of the most stable diatomic cations (D e = 11.0 eV) [7]. It is of importance in many ionospheric phenomena such as aurora [8] 0953-4075/98/173789+14$19.50 c 1998 IOP Publishing Ltd and is also present in large concentrations in the bow shock wave of spacecraft re-entering the Earth's atmosphere [9]. Despite this, the NO + cation is less studied spectroscopically than its isoelectronic counterparts, N 2 and CO molecules, mainly due to the difficulty in studying its band systems in the absorption spectra.…”
Section: Introductionmentioning
confidence: 99%
“…The cation of the NO molecule NO + is one of the most stable diatomic cations (D e = 11.0 eV) [7]. It is of importance in many ionospheric phenomena such as aurora [8] 0953-4075/98/173789+14$19.50 c 1998 IOP Publishing Ltd and is also present in large concentrations in the bow shock wave of spacecraft re-entering the Earth's atmosphere [9]. Despite this, the NO + cation is less studied spectroscopically than its isoelectronic counterparts, N 2 and CO molecules, mainly due to the difficulty in studying its band systems in the absorption spectra.…”
Section: Introductionmentioning
confidence: 99%
“…can give rise to the Baer-Miescher (BM) bands in the vacuum ultraviolet (VUV) auroral spectrum [Stone and Zipf, 1972]. Extensive theoretical computations have also shown that there can be other identifiable ultraviolet NO + emissions from auroras, although they have not yet been observed, possibly owing to blending with other, stronger emissions [Young et al, 1980]. Despite the importance to the study of auroral emissions, there have not been many laboratory experiments on the electron impact excitation of NO [Aarts and De Heer, 1971;Stone and Zipf, 1972;Mentall and Morgan, 1972].…”
mentioning
confidence: 99%